DESIGNING NEW TREND OF PESANTREN FOR SANTRI ENHANCEMENT IN RESPONSE TO GOLDEN INDONESIA VISION 2045 - Shulhan Shulhan (Reflektika, 2021)
Golden Indonesia is predicted to reach a tipping point in its development as a sovereign, advanced, just, and rich nation in 2045. The golden Indonesia 2045 Vision is supported by four pillars: Human development, scientific and technological mastery are prioritized, followed by sustainable economic development, equitable development, national resilience and government consolidation. Pesantren, as one of the oldest educational institutions in Nusantara, plays a key role in supporting the government in achieving the above-mentioned vision. The goal of this article is to look at the concept of a new pesantren trend for responding emerging issues in 2045 for succeeding the vision of a golden Indonesia. The research methodology used in this research was a qualitative method with library research. Academic texts (manuscripts) were used as primary data sources. The researcher intentionally applied the content-analyzed to read and analyze the data collected from the source mentioned above. The following were the study's findings: First, renewing the governance architecture of Islamic boarding schools entails: a. improving the quality of learning, which can enhance students' ability to read classical texts, memorize the Al-Quran, and increase a capacity in practicing Islamic religion and Islamic values in daily life; b. improving the quality of learning English, mathematics, and science; and c. providing adequate practice allocation supported by the availability of resources. Second, create new forecasts for pesantren graduates by requiring them to possess fundamental competencies, holistic integrative competences, and skills in cultivating the priority sectors tied directly to natural capital in the areas surrounding their homes.